Representativeness of European biochar research: part I – field experiments - Verheijen, Frank G. A.; Mankasingh, Utra; Penizek, Vit; Panzacchi, Pietro; Glaser, Bruno; Jeffery, Simon; Bastos, Ana Catarina; Tammeorg, Priit; Kern, Jürgen; Zavalloni, Costanza; Zanchettin, Giulia; Sakrabani, Ruben (Journal of Environmental Engineering and Landscape Management, 2017)
A representativeness survey of existing European Biochar field experiments within the Biochar COST Action TD1107 was conducted to gather key information for setting up future experiments and collaborations, and to minimise duplication of efforts amongst European researchers. Woody feedstock biochar, applied without organic or inorganic fertiliser appears over-represented compared to other categories, especially considering the availability of crop residues, manures, and other organic waste streams and the efforts towards achieving a zero waste economy. Fertile arable soils were also over-represented while shallow unfertile soils were under-represented. Many of the latter are likely in agroforestry or forest plantation land use. The most studied theme was crop production. However, other themes that can provide evidence of mechanisms, as well as potential undesired side-effects, were relatively well represented. Biochar use for soil contamination remediation was the least represented theme; further work is needed to identify which specific contaminants, or mixtures of contaminants, have the potential for remediation by different biochars.